Metabolomics analysis of aqueous humor from patients with high-myopia complicated nuclear cataract - Huo, Qiuyi; Xu, Yitong; Wang, Yaqi; Zhang, Shenrong; Liu, Zhexuan; Li, Jin (Frontiers in Medicine, 2025)
BackgroundWe investigated the metabolic profiles of aqueous humor (AH) among patients with high-myopia complicated nuclear cataract (HMnC), age-related nuclear cataract (NC), cortical cataract (CC), and high myopia (HM); we sought to identify possible metabolic mediators for these conditions.MethodsThe metabolic data of AH from 29 patients (nine with HMnC, nine with CC, seven with NC, and four with high myopia) were analyzed by liquid chromatography-tandem mass spectrometry. Principal component analysis, sample correlation analysis, and orthogonal partial least squares discriminant analysis modeling were conducted. Univariate and multivariate analyses were performed to identify differential metabolites with potential biological significance.ResultsFor HMnC patients, the level of glutathione was decreased, whereas arginine, tyrosine, and tryptophan were more abundant in AH. Dihomomethionine and 8-methylthiooctanaldoxime located in the methionine metabolic pathways were downregulated in NC samples compared with HMnC samples. Additionally, the levels of D-alanyl-D-alanine, 1-methylpyrrolinium, L-phenylalanine, ecgonine methyl ester, ecgonine, tropinone, and azacyclohexane, NNK-N-oxide, 3-succinoylpyridine, and N-nitrosodimethylamine were all upregulated in HM samples compared with HMnC samples.ConclusionThis work identified valuable metabolic biomarkers and pathways that may improve understanding HMnC pathogenesis. Here, we found that a decrease in glutathione might promote the occurrence of HMnC. Arginine, tyrosine, and tryptophan were more abundant in AH from HMnC patients and tended to prevent HMnC progression. These findings have translational value in terms of developing new therapeutic measures for HMnC-related complications.